Problem-based learning para o desenvolvimento da flexibilidade cognitiva no ensino de Física - Silva, Bruno Prates da (2024)
The research developed in this dissertation is centered on investigating the structuring and evaluation of a set of Physics Teaching Activities designed for an introductory Physics course in the undergraduate course in Chemical Engineering. These activities are structured based on the assumptions of the active methodology Problem-Based Learning and the perspective of the Cognitive Flexibility Theory, aiming at the development of cognitive flexibility by higher education students. To achieve this, initially, a Systematic Review of the Literature on Problem-Based Learning is carried out, situating the publications that involve its implementation in Physics Teaching and Science Education. Theoretical deepening is also carried out regarding the aforementioned methodology, as well as the Theory of Cognitive Flexibility. For the intended theoretical-methodological integration, a structuring tool called Learning Assistance Questions was developed. Using this tool, a set of Physics Didactic Activities is created that involves content relating to Hooke's law, Energy, Work, Linear Momentum and Collisions, within the scope of Classical Mechanics. To evaluate the research results, three dimensions of analysis are used: the learning objectives, the objectives of the Cognitive Flexibility Theory and the students' perceptions. The conclusions reveal an expansion of conceptual aspects, indicating their flexibility and contextual adaptation; Furthermore, they provide evidence of the achievement of criss-crossing landscape through the recognition and application of different themes in different contexts, elements that point to the development of cognitive flexibility.